Membangun Komitmen Kebangsaan Melalui Semangat Pela Gandong - Rumlus, Amandus Natalis Rento (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STPAK St. Yohanes Penginjil Ambon, 2025)
This research aims to explore the local wisdom of pela gandong as a cultural wealth of the Maluku community and to integrate it for enriching national commitment. Using qualitative research methods with primary and secondary data sources, this study discusses maintains that pela gandong has the potential to foster national commitment. The research findings indicate that pela gandong embodies values of community, social solidarity, equality, and peace. These values can be integrated with a commitment to nationalism, which aligns with the principles contained within it. In addition, this local wisdom serves as an effective conflict resolution tool in easing social tensions in Maluku from 1999 to 2004. This research also identifies challenges in preserving the values of pela gandong, including issues of religion and politics, social and environmental changes, modernization, globalization, and tensions within community life.